Prevalence of dietary supplement use and associated factors among female college students in Saudi Arabia - Hanan Alfawaz; Nasiruddin Khan; Aziza Alfaifi; Fatima M. Shahrani; Huda M. Al Tameem; Seetah F. Al Otaibi; Weaam I. Abudigin; Mohammad S. Al-Shayaa; Saad A. Al-Ghanim; Nasser M. Al-Daghri (BMC, 2017)
Abstract Background The economic boom in Saudi Arabia indirectly prompted the use of dietary supplements in the last two decades. Our aim is to investigate the prevalence of dietary supplement use and its association with sociodemographic/lifestyle characteristics among Saudi female students. Methods In this cross-sectional study, 534 female participants (≥19 years of age) completed a self-administered questionnaire that include sociodemographic and lifestyle characteristics, perceived health status, dietary supplement use, general awareness, attitudes and behavior. Results In all participants, the prevalence of dietary supplement use was 76.6% (n = 409). High level of education (p = 0.002) and more physical activity (p = 0.008) exhibited a significant positive association with users than to non-users. The frequency showed that beta-carotene (54.2%), chamomile (54.2%), and glucosamine (53.8%) were the most preferred diet supplements under the category "when needed". Cod liver oil (71.3%), omega 3 (68.3%), multi-vitamins (61.5%), ginseng (60%), and vitamin A (60%), were mostly used "from time to time". Multi-minerals (34.4%) were the preferred choice when it comes to daily use. The main reasons for supplement use were to "maintain healthy hair" and "injury and illness" (both 26.2%). About 38.4% were not aware and 30.3% disagree on differences taking supplements with or without consulting a medical professional. About 36.7% lack information about side effects while, 35.0% were unaware about any health effect of dietary supplements. Conclusion The prevalence of dietary supplement use was high in Saudi female students and was significantly associated with sociodemographic and lifestyle factors.